2011
DOI: 10.1007/s13318-011-0074-5
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the barriers to bioavailability of macrolide antibiotics in the rat

Abstract: The aim of this study was to compare the roles of gastrointestinal absorption and hepatic extraction as barriers to oral bioavailability for macrolide antibiotics erythromycin, clarithromycin, roxithromycin and telithromycin. In this study, the in vitro metabolic stability in rat liver microsomes and hepatocytes, as well as the in vivo pharmacokinetics in rats were determined following intravenous, intraportal, oral and intraduodenal routes of administration. Pharmacokinetic parameters were calculated for each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Previous in vivo findings from rat studies that utilized administration through oral dosing did not observe adverse effects of nisin (54). However, this might be explained by the fact that our study utilized injection into the circulatory system of whole animals, while rats were exposed through oral administration, which inevitably changes the bioavailability and potential adverse effects of a compound (55). Nisin has also been shown to be degraded by proteases in the digestive system (56).…”
Section: Discussionmentioning
confidence: 99%
“…Previous in vivo findings from rat studies that utilized administration through oral dosing did not observe adverse effects of nisin (54). However, this might be explained by the fact that our study utilized injection into the circulatory system of whole animals, while rats were exposed through oral administration, which inevitably changes the bioavailability and potential adverse effects of a compound (55). Nisin has also been shown to be degraded by proteases in the digestive system (56).…”
Section: Discussionmentioning
confidence: 99%
“…and by mouth (capsules) of solithromycin (sponsor data (Cempra) on file). Previous studies evaluating the bioavailability of clarithromycin and telithromycin in rats demonstrated that the limited oral bioavailability is primarily due to low intestinal availability rather than first‐pass metabolism in the liver . In addition, grapefruit juice, a selective intestinal CYP3A4 inhibitor, did not significantly affect the oral absorption of clarithromycin or telithromycin .…”
Section: Discussionmentioning
confidence: 81%
“…Kato et al reported that CYP3A4 substrates, which have a hepatic intrinsic clearance of 78 μl/min/mg microsomal protein, have low bioavailability because of intestinal first-pass metabolism [22]. The intrinsic metabolic clearances of CAM and TEL in the liver were low (<1 μl/min/mg microsomal protein) [14]. In addition, grapefruit juice, a selective intestinal CYP3A4 inhibitor, did not affect the oral absorption of CAM and TEL [9,24].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies show that because CAM and TEL are substrates of P-gp and CYP3A4, the oral bioavailability of CAM and TEL increases after concomitant administration of P-gp and CYP3A4 inhibitors such as ketoconazole and itraconazole [8,9]. Recently, Padovan et al reported that, because of the low intrinsic metabolic clearance of CAM and TEL in the liver, metabolic processes in the liver have a small impact on the oral absorption of these antibiotics [14]. However, the involvement of intestinal availability in the oral absorption of CAM and TEL in the presence of efflux transporters remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%